2020
DOI: 10.1002/dad2.12047
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of prodromal and Alzheimer's disease dementia in adults with Down syndrome using neuropsychological tests

Abstract: Introduction We aimed to define prodromal Alzheimer's disease (AD) and AD dementia using normative neuropsychological data in a large population‐based cohort of adults with Down syndrome (DS). Methods Cross‐sectional study. DS participants were classified into asymptomatic, prodromal AD and AD dementia, based on neurologist's judgment blinded to neuropsychological data (Cambridge Cognitive Examination for Older Adults with Down's syndrome [CAMCOG‐DS] and modified Cued Recall Test [mCRT]). We compared the cutof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(83 citation statements)
references
References 36 publications
(85 reference statements)
5
78
0
Order By: Relevance
“…Benejam [18] and as expected, participants with ID with prodromal AD and AD dementia had worse scores than asymptomatic subjects. These authors also recommend cut-off points for the CAMCOG-DS for a diagnosis of prodromal AD and AD dementia in adults with DS, based on population norms stratified by level of ID impairment: mild ID, a score of 80 and moderate ID, scores of 56.…”
Section: Cross-sectional Studies In Participants With Down Syndromesupporting
confidence: 79%
See 1 more Smart Citation
“…Benejam [18] and as expected, participants with ID with prodromal AD and AD dementia had worse scores than asymptomatic subjects. These authors also recommend cut-off points for the CAMCOG-DS for a diagnosis of prodromal AD and AD dementia in adults with DS, based on population norms stratified by level of ID impairment: mild ID, a score of 80 and moderate ID, scores of 56.…”
Section: Cross-sectional Studies In Participants With Down Syndromesupporting
confidence: 79%
“…This inter-test reliability remained after removing MMSE related items in the CAMCOG-DS and excluding participants who achieved zero scores (r=.95). Furthermore, recent research has identified recommended cut-off points for the CAMCOG based on a normative sample of adults with DS[18]. However, it has been noted that this measure may not be suitable for those with severe learning disabilities, severe sensory impairments,…”
mentioning
confidence: 99%
“…Although DLD has been used in most studies showing it to be effective in identifying changes over time in people with DS and other ID [ 45 ], one study [ 51 ] revealed that it may not be an appropriate measure to assess dementia in people with severe ID. Recently, DLD was used in Benejam [ 18 ] and as expected, participants with ID with prodromal AD and AD dementia had worse scores than asymptomatic subjects. These authors also recommend cut-off points for the CAMCOG-DS for a diagnosis of prodromal AD and AD dementia in adults with DS, based on population norms stratified by level of ID impairment: mild ID, a score of 80 and moderate ID, scores of 56.…”
Section: Discussionmentioning
confidence: 82%
“…This inter-test reliability remained after removing MMSE related items in the CAMCOG-DS and excluding participants who achieved zero scores ( r = 0.95). Furthermore, recent research has identified recommended cut-off points for the CAMCOG based on a normative sample of adults with DS [ 18 ]. However, it has been noted that this measure may not be suitable for those with severe learning disabilities, severe sensory impairments, or advanced dementia due to floor effects [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation